2013
DOI: 10.4236/ajps.2013.48a006
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Rind Hardness on Sugarcane Quality

Abstract: Sugar recovery in a factory depends upon regular crushing and quality of varieties besides various other working parameters. Strategies for increased productivity and sugar recovery, varietal improvement can bring out through selection of parents to get maximum gains. These are governed by sugar content, fiber, rind hardness and cane yield. In order to assess the breeding value of different traits including rind hardness, study was undertaken at Sugarcane Research Institute, Shahjahanpur, during 2011-2012. Phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
1
0
1
Order By: Relevance
“…Positive and highly significant correlations exicted between sugar recovery % and sugar yield at the phenotypic level. Singh et al (2013) showed significant and positive genotypic correlations between sugar yield and each of cane weight, cane yield, brix % and sucrose %.…”
Section: Interrelationships Among Yield and Agronomic Traitsmentioning
confidence: 96%
“…Positive and highly significant correlations exicted between sugar recovery % and sugar yield at the phenotypic level. Singh et al (2013) showed significant and positive genotypic correlations between sugar yield and each of cane weight, cane yield, brix % and sucrose %.…”
Section: Interrelationships Among Yield and Agronomic Traitsmentioning
confidence: 96%
“…Hal ini menunjukkan bahwa pemberian PGPR mampu menurunkan kebutuhan vermikompos serta meningkatkan nilai diameter batang tanaman tebu. Hasil tebu berkorelasi positif dengan diameter tebu, jumlah anakan dan brix (Singh et al, 2013). Diameter batang dapat mencapai maksimal apabila lingkungan tumbuh tebu optimal.…”
Section: Diameter Batangunclassified
“…Prior work indicates that cultivar resistance may operate similarly between the two borer species [24] with some deviations (such as the HoCP 04-838 cultivar, which is resistant to SCB but not MRB) [25]. One aspect in determining the extent of cultivar resistance to either borer species is stalk fiber content, often associated with rind hardness [26,27]. The relationship between fiber and borer resistance has also been reported for other stem borer species in sugarcane [28,29], as well as in other poaceous crops such as maize [30][31][32] and sorghum [33,34].…”
Section: Introductionmentioning
confidence: 99%